Influence of Calcium Doping on the Structural, Vibrational and Optical Properties of Nickel Ferrite - Dube, Punam B.; Uable, Yogesh P.; Saraf, Tukaram; Garud, Dilip; Jadhav, K.M. (Asian Journal of Chemistry, 2026)
Calcium-doped nickel ferrite (Ni1-xCaxFe2O4, x = 0.00, 0.05, 0.10, 0.15, 0.20) nanoparticles were synthesised using citric acid assisted sol-gel auto combustion method. X-ray diffraction (XRD) analysis confirmed the formation of a cubic spinel structure with single phase. Crystallite size obtained from Scherrer equation is in the range of 21 to 16 nm. An increase in lattice constant from 8.336 to 8.353Å with calcium doping is observed. FTIR spectra indicated typical metal-oxygen bond vibrations with absorption band located near at 600-400 cm–1. Raman spectra revealed significant changes in vibrational modes (T2g(1), Eg, T2g(2), T2g(3) and A1g(1)) due to the calcium doping. Morphological studies using SEM displayed a uniform grain growth with small agglomeration of nanoparticles. Grain size calculated from intercept method was 32.57 nm for bare nickel ferrite and 31.5 nm for Ca doped nickel ferrite (x = 0.10). TEM analysis revealed uniformly shaped nanoparticles, while the corresponding selected area electron diffraction (SAED) patterns confirmed the high crystallinity and phase purity of the synthesized samples. The optical absorption characteristics were examined using UV-Vis spectroscopy and Tauc plot analysis yielded band gap values between 1.74 and 1.78 eV. These findings demonstrate that calcium doping markedly influences the structural, vibrational, morphological and optical properties of nickel ferrite nanoparticles.